2017
DOI: 10.2196/jmir.6716
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Efficiency of Online and Offline Recruitment Methods: A Web-Based Cohort Study

Abstract: BackgroundThe Internet is widely used to conduct research studies on health issues. Many different methods are used to recruit participants for such studies, but little is known about how various recruitment methods compare in terms of efficiency and costs.ObjectiveThe aim of our study was to compare online and offline recruitment methods for Internet-based studies in terms of efficiency (number of recruited participants) and costs per participant.MethodsWe employed several online and offline recruitment metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 29 publications
(75 reference statements)
6
94
0
Order By: Relevance
“…An online survey was created utilizing the Qualtrics survey platform (Qualtrics, ). Research suggests that online recruitment methods are superior to offline methods in terms of efficiency and cost (Christensen, Riis, Hatch, Wise, & Marie, ) and result in larger voice‐hearing sample sizes (Berry, Band, Corcoran, Barrowclough, & Wearden, ; Lawrence, Jones, & Cooper, ). Those choosing to take part in the survey were asked to read the study information and provide informed consent prior.…”
Section: Methodsmentioning
confidence: 99%
“…An online survey was created utilizing the Qualtrics survey platform (Qualtrics, ). Research suggests that online recruitment methods are superior to offline methods in terms of efficiency and cost (Christensen, Riis, Hatch, Wise, & Marie, ) and result in larger voice‐hearing sample sizes (Berry, Band, Corcoran, Barrowclough, & Wearden, ; Lawrence, Jones, & Cooper, ). Those choosing to take part in the survey were asked to read the study information and provide informed consent prior.…”
Section: Methodsmentioning
confidence: 99%
“…Adam et al [60] recruited almost 10 times the number of pregnant women per day using social media than through traditional recruitment methods similar to those employed in the current study, but also found that women recruited via social media were less likely to participate in their trial comparing counseling to standard care for management of appropriate pregnancy-related weight gain. Similarly, Christensen et al, [61] recruited women trying to conceive to a nutrition and lifestyle study. They used o ine and online methods to recruit, including Facebook ads.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted advertisements (e.g., filtered by age, gender, and smartphone usage) ensures that advertisements will reach the target group. While online recruitment is not necessarily superior to offline recruitment, the combination of both approaches was found to be optimal for achieving a representative sample ( 39 ). Therefore, efforts will be undertaken to recruit participants in the community, including placing newspaper advertisements, emails to health professionals and civic organizations, media and press releases at Charité Universitätsmedizin Berlin.…”
Section: Materials and Equipmentmentioning
confidence: 99%